Enhancing Data Collection and Climate Monitoring with the AICCRA KMD Mobile App and Web Dashboard - Akshatha, Annaiah (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The AICCRA-KMD is a Data Collection Android Mobile App is a collaborative effort between KMD and ILRI under Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA).